2022
DOI: 10.1111/gcb.16231
|View full text |Cite
|
Sign up to set email alerts
|

Microbiome assembly in thawing permafrost and its feedbacks to climate

Abstract: The physical and chemical changes that accompany permafrost thaw directly influence the microbial communities that mediate the decomposition of formerly frozen organic matter, leading to uncertainty in permafrost-climate feedbacks. Although changes to microbial metabolism and community structure are documented following thaw, the generality of post-thaw assembly patterns across permafrost soils of the world remains uncertain, limiting our ability to predict biogeochemistry and microbial community responses to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
32
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 56 publications
(32 citation statements)
references
References 203 publications
(292 reference statements)
0
32
0
Order By: Relevance
“…Drift is the core of fungal community assembly ( Sheng et al, 2019 ). As plant diversity increases and input soil nutrients, the dominance of deterministic processes leads to a community well adapted to environmental conditions ( Ernakovich et al, 2022 ). These findings are supported by the results of the neutral model, which indicated that the mixture system led to higher environmental selection, indicating that a reduced degree of dispersal resulted from biological factors associated with increasing plant richness ( Supplementary Figure 5 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Drift is the core of fungal community assembly ( Sheng et al, 2019 ). As plant diversity increases and input soil nutrients, the dominance of deterministic processes leads to a community well adapted to environmental conditions ( Ernakovich et al, 2022 ). These findings are supported by the results of the neutral model, which indicated that the mixture system led to higher environmental selection, indicating that a reduced degree of dispersal resulted from biological factors associated with increasing plant richness ( Supplementary Figure 5 ).…”
Section: Discussionmentioning
confidence: 99%
“…These findings are supported by the results of the neutral model, which indicated that the mixture system led to higher environmental selection, indicating that a reduced degree of dispersal resulted from biological factors associated with increasing plant richness ( Supplementary Figure 5 ). Conversely, stochastic processes increase the number of maladapted taxa and may reduce ecosystem function for some microbiomes ( Ernakovich et al, 2022 ). In addition, selection would lead to more similar phylogenetic groups and make their communities better aligned against external disturbances ( Yu et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…The terrestrial and subsea permafrost regions contain nearly 3,000 Gt of organic carbon, more than the sum of all other soil, the atmosphere, living biomass, and cumulative human emissions since the Industrial Revolution . These massive stocks of organic matter have been described as climate-protected, as they have been stabilized by persistent cold and wet conditions, which limit microbial and abiotic decomposition (Ernakovich et al 2022;. Gradual climate warming after the Last Glacial Maximum (LGM), some 26,500 years ago, resulted in over 100 meters of sea level rise, retreat of ice sheets, and widespread development of lakes and peatlands .…”
Section: Case Study 3: Paleo and Present Climate Change Effects On Th...mentioning
confidence: 99%
“…Equally as concerning is the observation that permafrost thaw releases ancient and novel pathogens entrapped as sub-zero microbiotome in permafrost ice for centuries [37,38] . Permafrost pathogens include parasites and fungi [39] , bacteria [40] , as well as DNA [41] , RNA [42] and giant viruses [43] . Taken together, the release of novel and ancient pathogens by melting permafrost poses timely and critical challenges to our immune system [44] , which is generally ill-equipped to confront new microbes, as the recent and ongoing pandemic confirms.…”
Section: Novel and Ancients Pathogens In Melting Permafrostmentioning
confidence: 99%